Survival of Fusarium moniliforme in soil, grains and stubbles of paddy - SATYAVIR2, S. SUNDER1 and (Indian Phytopathology, 2002)
Fusarium moniliforme (bakanae pathogen) could survive for considerably longer period in infected grains and stubbles of paddy stored at room temperature in Haryana. It had survived for 26 months in grains of cultivar Haryana Gaurav and for 16 months in those of Taraori Basmati and Basmati 370. F. moniliforme was found associated with none of the stubbles .after 14 and 18 months of storage in unsterilized and sterilized soil, respectively, however, it could survive for 26 and 28 months in dried stubble-pieces of Haryana Gaurav and Taraori Basmati stored independently of the soil. In soil infested with fungal propagules, the population of the pathogen increased initially for two months and could be detected only for 10 and 13 months from unsterilized and sterilized soil, respectively.